Information and Communication Technologies for Effective Communication in Older Adults (Journal on studies and research of academic knowledge, 2024)
Technology should not be the privilege only of young people; it should reach with all its importance to older adults, therefore, the need arose to integrate older adults in the field of Technology, learning with young people/students of the Faculty of Applied Sciences-Pilar-Paraguay, for effective communication among their peers, family members, etc. The study consisted of a literature review, conducted between the years 2015 to 2022, through a search process of scientific articles. The results allowed identifying the values of justice, respect, tolerance, dialogue and also the inclusion of technology, in daily life as a tool to strengthen family ties between older adults, youth and grandchildren, combining the playful component of mobile devices with educational content in family values. The purpose was achieving integration among older adults, youth and grandchildren of families living and residing in the City of Pilar, as well as fostering a positive attitude towards technology that provides an essential support to simplify their lifestyle.